The Influence Of Work Experience And Educational Level On The Auditor's Ability To Detect Fraud Through Professional Skeptism Auditors (Study at the Public Accounting Office of Makassar City) - Syamsuri Rahim; Muslim Muslim; Muftihaturrahmah Muftihaturrahmah (SEAN Institute, 2023)
This research aims to examine the influence of work experience and level of education on the auditor's ability to detect fraud through the professional skepticism of auditors at KAP in Makassar. The data in this research was obtained from each KAP in Makassar City who were willing to be respondents. This research uses primary data by conducting direct research in the field by providing questionnaires/question sheets to 34 respondents. The data analysis method used is multiple linear regression analysis which is processed using the SPSS-20 program.The research results show that partially work experience has a positive and significant influence on the auditor's ability to detect fraud, education level has a positive and significant influence on the auditor's ability to detect fraud, and professional skepticism influences the auditor's ability to detect fraud. Meanwhile, the intervening variable, namely work experience, has a positive and significant influence on the auditor's ability to detect fraud through the auditor's professional skepticism and the level of education has a positive and significant influence on the auditor's ability to detect fraud through the auditor's professional skepticism. This research aims to examine the influence of work experience and level of education on the auditor's ability to detect fraud through the professional skepticism of auditors at KAP in Makassar. The data in this research was obtained from each KAP in Makassar City who were willing to be respondents. This research uses primary data by conducting direct research in the field by providing questionnaires/question sheets to 34 respondents. The data analysis method used is multiple linear regression analysis which is processed using the SPSS-20 program.The research results show that partially work experience has a positive and significant influence on the auditor's ability to detect fraud, education level has a positive and significant influence on the auditor's ability to detect fraud, and professional skepticism influences the auditor's ability to detect fraud. Meanwhile, the intervening variable, namely work experience, has a positive and significant influence on the auditor's ability to detect fraud through the auditor's professional skepticism and the level of education has a positive and significant influence on the auditor's ability to detect fraud through the auditor's professional skepticism.